The Impact of a "Clinical Adaptation Psychoeducation Program" Grounded in the Psychological Flexibility Model on Perceived Stress and Coping Behaviors Among Nursing Students: A Randomized Controlled Experimental Study - Tunc, Ercan; Orak, Oya Sevcan (Churchill Livingstone, 2024)
Background: The clinical adaptation psychoeducation program grounded psychological flexibility model (PFMCAP) is consisting of six areas, fills a large gap in the literature regarding the effect of nursing students on perceived stress and coping behaviors in the clinical process. Objectives: To determine the effect of PFMCAP on perceived stress and coping behaviors of nursing students. Design: This was a simple randomized controlled experimental pre-posttest design. Setting: This study was conducted with 66 first-year students studying in the nursing department of a university in T & uuml;rkiye. Methods: A simple randomization method (computer-generated random number table) was used. Data were collected with "Sociodemographic Data Form", "Perceived Stress Scale for Nursing Students (PSSNS)" and "Stress-Coping Behaviors Scale for Nursing Students (SCBNS)". PFMCAP was conducted online with first-year nursing students, consisting of a total of six sessions, each lasting 90 min. Data were analyzed using percentiles and frequency distributions, and two-way mixed ANOVA one week after the completion of the PFMCAP. Results: There was no significant difference between the groups of descriptive characteristics (p > 0.05). Post-test measurements of students in the experimental group's PSSNS total and sub-dimension scores had a significant decrease compared to the control group (p < 0.001). There was no significant difference between the groups in the post-test SCBNS total scores of the students (p > 0.05). However, there was a significant increase in the posttest SCBNS-Staying Optimistic sub-dimension scores in the experimental group (p < 0.001). Conclusion: The impact of PFMCAP on nursing students' perceived stress levels was not limited to only reducing stress levels; it also contributed to an increase in the students' levels of optimism. These findings demonstrate the potential of PFMCAP in supporting nursing students during the clinical adaptation process. It is observed that the integration of PFMCAP into nursing education could assist nursing students in better adapting to clinical practices and effectively managing stress.
Orak, Oya Sevcan/0000-0002-7499-5077; Tunç, Ercan/0000-0002-3485-953X;
Keywords: Perceived Stress; Coping Behavior; Nursing Students; Clinical Compliance; Psychoeducation; Psychological Flexibility Model